2010
DOI: 10.1097/ta.0b013e3181fa0019
|View full text |Cite
|
Sign up to set email alerts
|

Duration of Red Cell Storage Influences Mortality After Trauma

Abstract: Background Although previous studies have identified an association between the transfusion of relatively older red blood cells (RBCs) (storage ≥14 days) and adverse outcomes, they are difficult to interpret because the majority of patients received a combination of old and fresh RBC units. To overcome this limitation, we compared in-hospital mortality among patients who received exclusively old versus fresh RBC units during the first 24 hours of hospitalization. Methods Patients admitted to a Level I trauma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
165
3
4

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 117 publications
(180 citation statements)
references
References 26 publications
8
165
3
4
Order By: Relevance
“…Regulations in many countries specify 42 days (6 weeks) as the shelf life for stored red blood cells (RBCs), and a first-in-first-out inventory management approach is standard. Large-scale clinical studies involving 200-1800 patients indicated that patients transfused with older RBCs tend to have a higher risk of mortality than those receiving fresher RBCs [1][2][3][4] .…”
Section: Introductionmentioning
confidence: 99%
“…Regulations in many countries specify 42 days (6 weeks) as the shelf life for stored red blood cells (RBCs), and a first-in-first-out inventory management approach is standard. Large-scale clinical studies involving 200-1800 patients indicated that patients transfused with older RBCs tend to have a higher risk of mortality than those receiving fresher RBCs [1][2][3][4] .…”
Section: Introductionmentioning
confidence: 99%
“…Our search strategy is shown in Figure 2. 31 Murrell et al 36 Phelan et al 35 Spinella et al 32 Weinberg et al 33 Weinberg et al 30 Weinberg et al 34 No Definitions for the age of stored blood varied among the 7 studies. Blood was considered old if it was in storage 14 days or longer, 30,33,34 longer than 14 days, 31 or 28 days or longer.…”
Section: Resultsmentioning
confidence: 99%
“…31 Murrell et al 36 Phelan et al 35 Spinella et al 32 Weinberg et al 33 Weinberg et al 30 Weinberg et al 34 No Definitions for the age of stored blood varied among the 7 studies. Blood was considered old if it was in storage 14 days or longer, 30,33,34 longer than 14 days, 31 or 28 days or longer. 32 One study 35 used the mean age of all units received within 14 days to define new blood and the mean age of all units stored 21 days or longer to define old blood, and 1 study 36 developed a composite variable that was defined by the proportionate age of each blood unit averaged over all units transfused and then multiplied by the total number of units transfused.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…14,15 Although the current "shelf life" of stored blood is 42 days, there is evidence that after some duration of RBC storage, perhaps even 15-21 days, the capacity for tissue oxygen delivery is diminished. [16][17][18] In fact, studies have described adverse outcomes, 19,20 including increased mortality, 21,22 in patients who receive blood that has been stored for longer durations. Another concern is the potential adverse effects of cardiopulmonary bypass (CPB) and the resulting injury to the RBC cell membrane.…”
Section: Introductionmentioning
confidence: 99%